The implementation of discussion method to improve Learning outcomes andstudents’ ipsachivement on Fifth grade student at sd negeri 15 lansano in the District sutera pesisir selatan regency - Amyarnis Amyarnis (Jurnal Ilmiah Pendidikan Scholastic, 2017)
ass Action Research Lansano 15 V Elementary School District of Sutera at the beginning of January’ to March 201 7. Results of study Social Sciences class V SD Negeri 15 Lansano District of Sutera of several replications are still very low. Of the two repetitions the average grade is still below the KKM is 75. The highest score of 70 while the lowest value 50. On the second daily test of 80 and the lowest score 50. The average of the two daily test is 67. The purpose of this study is to improve learning outcomes IPS with the basic competencies' to describe the struggle of the hero on the Dutch and Japanese invaders ". B erdasarkan struggle of the hero on the Dutch and Japanese invaders in the learning of Social Sciences for the fifth grade students of SD Negeri 15 Lansano District of Sutera 2nd semester through themethod of discussion. Research conducted at SDN 15 Lansano District of Sutera. Time research was conducted from January to March 201 7. The form of this research is Classroom Action Research (Classroom Action Research). The action consists of two actions in two cycles. Each cycle consists of four stages namely Planning, acting, observing, and reflecting. The class is fifth grade students studied Elementary School # 15 Lansano District of Sutera with the number of students 29 orang.Setelah implemented the first cycle that teachers implement instructional practices directly obtained results In cycle 1 the average grade value increased to 75. In cycle 2 the average value was 86. So from the initial to the final condition there was an increase in learning outcome from the mean of 67 to 86. From the results of the action research conducted in two cycles, obtained significant improvement, so that it can be concluded that the discussion of methods to improve learning outcomes IPS is based on the struggle of the hero in the Netherlands and the Japanese invaders for fifth grade students of SD Negeri 15 Lansano Subdistrict Sutera. For that teachers are expected to always provide guidance to students to remain diligent learning, through reading, discussing to always practice working on student worksheets, so it can achieve the desired goals